Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1126
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Speaker Variability: Speaker Normalisation and Quantitative Estimation of Articulatory Invariants in Speech Production for French

Abstract: Speech production can be analysed in terms of universal articulatory-acoustic phonemic units shared between speakers. However, morphological differences between speakers and idiosyncratic articulatory strategies lead to large inter-speaker articulatory variability. Relationships between strategy and morphology have already been pinpointed in the literature. This study aims thus at generalising existing results on a larger database for the entire vocal tract (VT) and at quantifying phoneme-specific inter-speake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sec. I), including by Serrurier et al (2017) with the same data. The fact that no significant correlation (above 0.5) between MP2 and the strategy predictors and between S2 and the morphology predictors suggests that either speakers do not always adapt their strategies to their morphological characteristics or that these relations are not captured by the present linear modelling approach.…”
Section: B Articulatory Strategy Characterizationmentioning
confidence: 99%
“…Sec. I), including by Serrurier et al (2017) with the same data. The fact that no significant correlation (above 0.5) between MP2 and the strategy predictors and between S2 and the morphology predictors suggests that either speakers do not always adapt their strategies to their morphological characteristics or that these relations are not captured by the present linear modelling approach.…”
Section: B Articulatory Strategy Characterizationmentioning
confidence: 99%
“…In the study by Stone et al (2016), the muscle architectures of different subjects were investigated. Speaker normalization was performed by Geng and Mooshammer (2009) and Serrurier et al (2017).…”
Section: Related Workmentioning
confidence: 99%
“…In this regard, articulatory information is known to be less affected by noise and contains speaker identity information, so it is prone to be used in automatic speaker recognition tasks [13]. Furthermore, several studies have shown articulatory related information is an important source of variability between speakers [13][14][15]. Nevertheless, measuring articulatory information is a complex task, and there are alternative strategies that have been proposed to estimate articulatory movements using acoustic information [16][17][18].…”
Section: Introductionmentioning
confidence: 99%